Micropropagation of Withania somnifera Using Shoot Tip Explants (Plant Tissue Culture and Biotechnology, 2026)
In the present investigation in vitro propagation of a rare medicinal plant, Withania somnifera was carried out. Direct regeneration achieved from shoot tip explants and shoot multiplication was obtained by using cytokinin BAP (2.0 μM /l) and combination of BAP (2.0 μM /l) + IBA (2.0 μM/l), respectively. MS media with shoot tip explants supplemented with BAP (2.0 μM/l) produced maximum average number of shoots (5 ± 0.53) and average shoot length was found to b 2.5 ± 0.15 cm. significant induced were sub cultured in shoot multiplication, developed shoot multiplication was obtained average number of shoots (5.3 ± 0.41) and average shoot length 6.5 ± 0.12 cm was shown on MS media in combination with BAP (4.0 μM) + IBA (2.0-8.0 μM/l). Maximum average number (6 ± 0.10) and average length 7.6 ± 0.18 cm of roots were observed on MS media supplemented with IBA (2.0 um/l).  The MS medium supplemented with BAP and Kn was formed to be suitable for in vitro propagation of W. somnifera.Plant Tissue Cult. & Biotech. 35(2): 229-236, 2025 (December)